A radiological assessment of the quality of reduction of distal radius fractures at Charlotte Maxeke Johannesburg Academic Hospital - Minnis, Akin A. (My University, 2018)
Distal radius fractures are one of the commonest injury types encountered by an orthopaedic surgeon. At Charlotte Maxeke Johannesburg Academic Hospital (CMJAH), patients are exposed to a surgical staff with different levels of experience. Adequate assessment and management are of paramount importance in improving the chances of a good functional outcome. The primary purpose of this study was to assess the quality of reduction of acute distal radius fractures at our institution CMJAH using the universally accepted parameters of distal radius morphology, to determine if surgeon’s experience level influences the quality of reductions of distal radius fractures and secondarily, to ascertain if our surgeon based management reflects the suggested management of the IDEAL classification system. An observational prospective review was performed. Twenty-six (26) patients with DRF’s were treated at CMJAH over a six-month period and their pre- and postreduction radiographs were assessed for the adequacy of reduction using manual measurements with standardised goniometer and ruler. Comparisons were made between the various surgeons’ experience levels and the surgeons’ management strategy was compared to the IDEAL classification. Descriptive statistics, paired sample tests, tests of normality, analysis of variance, and paired proportions were used to analyse the data. All radiological parameters assessed demonstrated a statistically significant degree of reduction (p<0.05). There was good interobserver agreement in all of the radiographic parameters assessed except radial height and lateral articular gap (p>0.05). The surgeon’s choice of reduction method closely resembles that suggested by the IDEAL Classification System. We concluded that distal radius fractures presenting to CMJAH casualty over a sixmonth period were adequately reduced. The surgeon’s level of experience may impact the quality of reduction of the radial height. The IDEAL classification may prove v       useful as an alternative in classifying and guiding management at our institution. Outcome studies of this cohort are required to determine if our statistically significant reductions are functionally significant.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Orthopaedic Surgery, 2018
Keywords: Radius (Anatomy)--Fractures; Fractures